International Students’ Likelihood to Seek Counseling while Studying Abroad - Onabule, Adebayo I.; Boes, Susan R. (Journal of International Students, 2013)
International students experience significant stressors while studying in American colleges and universities, yet they use psychological services far less than domestic students (Misra & Castillo, 2004). Factors such as previous experience with counseling, perceived effectiveness of counseling style, and nationality were found to be factors affecting international students’ use of counseling services (Dadfar & Friedlander’s, 1982; Mori, 2000; Hyun, Quinn, Madon, & Lustig, 2007). This action research study adds to the literature by presenting suggestions about the manner in which international students may be most effectively served by their campus counseling centers, using information drawn from a focus group and a survey.